Expressions of sceptical topoi in (late) antique Judaism - Ḳiperṿaser, Reuven 1960-; Herman, Geoffrey 1967- (Berlin De Gruyter, 2021)
Frontmatter -- Contents -- Introduction -- Doubting Divine Justice and Human Knowledge: Qohelet's Cultural Dialectics -- "Matters That Tend towards Heresy": Rabbinic Ways of Reading Ecclesiastes -- Wisdom Scepticism and Apocalyptic Certitude; Philosophical Certitude and Apocalyptic Scepticism -- Reasonable Doubts of the "Other": Jewish Scepticism in Early Christian Sources -- Idolatry, God(s), and Demons among the Jews of Sasanian Babylonia -- Facing Omnipotence and Shaping the Sceptical Topos -- "If a Man Would Tell You" -- List of Contributors -- Index of Names and Places -- General Index
Scepticism has been the driving force in the development of Greco-Roman culture in the past, and the impetus for far-reaching scientific achievements and philosophical investigation. Early Jewish culture, in contrast, avoided creating consistent representations of its philosophical doctrines. Sceptical notions can nevertheless be found in some early Jewish literature such as the Book of Ecclesiastes. One encounters there expressions of doubt with respect to Divine justice or even Divine involvement in earthly affairs. During the first centuries of the common era, however, Jewish thought, as reflected in rabbinic works, was engaged in persistent intellectual activity devoted to the laws, norms, regulations, exegesis and other traditional areas of Jewish religious knowledge. An effort to detect sceptical ideas in ancient Judaism, therefore, requires a closer analysis of this literary heritage and its cultural context.This volume of collected essays seeks to tackle the question of scepticism in an Early Jewish context, including Ecclesiastes and other Jewish Second Temple works, rabbinic midrashic and talmudic literature, and reflections of Jewish thought in early Christian and patristic writings. Contributors are: Tali Artman, Geoffrey Herman, Reuven Kiperwasser, Serge Ruzer, Cana Werman, and Carsten Wilke
Keywords: Judentum; Maimonides; Mittelalter; Philosophie; Islam; History / Jewish; Scepticism, Early Judaism, Rabbinic Judaism; Aufsatzsammlung; Konferenzschrift -- 2016 -- Hamburg